2013
DOI: 10.1093/mnras/stt1037
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental parameters of 16 late-type stars derived from their angular diameter measured with VLTI/AMBER★

Abstract: Thanks to their large angular dimension and brightness, red giants and supergiants are privileged targets for optical long-baseline interferometers. Sixteen red giants and supergiants have been observed with the VLTI/AMBER facility over a two-years period, at medium spectral resolution (R = 1500) in the K band. The limb-darkened angular diameters are derived from fits of stellar atmospheric models on the visibility and the triple product data. The angular diameters do not show any significant temporal variatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 103 publications
3
29
4
Order By: Relevance
“…The literature values can vary (see e.g. Dehaes et al 2011;Cruzalèbes et al 2013;Jönsson et al 2014), but will not influence our conclusions. We use the sets of evolutionary tracks from Bertelli et al (2008Bertelli et al ( , 2009) who use isochrones from Girardi et al (2000).…”
Section: Stellar Parametersmentioning
confidence: 97%
“…The literature values can vary (see e.g. Dehaes et al 2011;Cruzalèbes et al 2013;Jönsson et al 2014), but will not influence our conclusions. We use the sets of evolutionary tracks from Bertelli et al (2008Bertelli et al ( , 2009) who use isochrones from Girardi et al (2000).…”
Section: Stellar Parametersmentioning
confidence: 97%
“…at a few mas distance. Most recently, Cruzalèbes et al (2013) presented evidence that there is a departure from centrosymmetry based on VLTI/AMBER data. On the other hand, MIDI interferometry carried out by Klotz et al (2013) was found to be consistent with a spherical structure of the star and its circumstellar envelope.…”
Section: The Targetmentioning
confidence: 99%
“…The investigation of AGB stars using a combination of different techniques has been increasing over the last few years, while, to date, only a few interferometric observations of carbon stars have been directly compared with model atmospheres (Ohnaka et al 2007;Paladini et al 2011;Cruzalèbes et al 2013;Klotz et al 2013;van Belle et al 2013). From those, only very few have made use of time-dependent self-consistent dynamic models (Sacuto et al 2011;Rau et al 2015).…”
Section: Introductionmentioning
confidence: 99%